2023
DOI: 10.1530/jme-22-0105
|View full text |Cite
|
Sign up to set email alerts
|

The epidermal growth factor receptor in healthy pregnancy and preeclampsia

Abstract: The epidermal growth factor receptor (EGFR) is expressed robustly in the placenta, and critical processes of pregnancy such as placental growth and trophoblast fusion are dependent on EGFR function. However, the role that aberrant EGFR signaling might play in the etiology and/or maintenance of preeclampsia (PE) remains largely unexplored. Recently, we have shown that overexpression of EGFR in cultured uterine artery endothelial cells (UAEC), which express little endogenous EGFR, remaps responsiveness away from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 134 publications
0
1
0
Order By: Relevance
“…We found that each macrophage subtype was rich in transcripts encoding cytokines, chemokines, and growth factors that could plausibly promote EVT invasion or otherwise signal to fetal trophoblasts. AREG and EREG signal to EGFR, which has been shown in several studies to regulate normal and adverse outcomes of pregnancy, as has VEGF ( 89 , 90 ). GPNMB promotes proliferation, invasion and metastasis of tumor cells ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that each macrophage subtype was rich in transcripts encoding cytokines, chemokines, and growth factors that could plausibly promote EVT invasion or otherwise signal to fetal trophoblasts. AREG and EREG signal to EGFR, which has been shown in several studies to regulate normal and adverse outcomes of pregnancy, as has VEGF ( 89 , 90 ). GPNMB promotes proliferation, invasion and metastasis of tumor cells ( 70 ).…”
Section: Discussionmentioning
confidence: 99%